2011
DOI: 10.1155/2011/934910
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Ischial Pressure Ulcers: I. Review of Neuromuscular Electrical Stimulation

Abstract: Abstract.Objective: Pressure ulcers (PUs) are common and debilitating wounds that arise when immobilized patients cannot shift their weight. Treatment is expensive and recurrence rates are high. Pathophysiological mechanisms include reduced bulk and perfusion of chronically atrophic muscles as well as prolonged occlusion of blood flow to soft tissues from lack of voluntary postural shifting of body weight. This has suggested that PUs might be prevented by reanimating the paralyzed muscles using neuromuscular e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…While interface pressure mapping is commonly used to assess NMES for PUP, an important drawback has been that the variations in peak pressure have usually been reported for only very small areas immediately beneath the ischial tuberosities (e.g. a single cell of 1.3×1.3 = 1.6 cm 2 [23,24], or a zone of 3.6×3.6 = 13 cm 2 [11,28]; see review in companion paper I [14]). However large areas are at risk if the closed capillaries are not able to reperfuse through adequate unloading, and the ability to recover from ischemic damage may depend on mass effects.…”
Section: Surface Stimulation Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…While interface pressure mapping is commonly used to assess NMES for PUP, an important drawback has been that the variations in peak pressure have usually been reported for only very small areas immediately beneath the ischial tuberosities (e.g. a single cell of 1.3×1.3 = 1.6 cm 2 [23,24], or a zone of 3.6×3.6 = 13 cm 2 [11,28]; see review in companion paper I [14]). However large areas are at risk if the closed capillaries are not able to reperfuse through adequate unloading, and the ability to recover from ischemic damage may depend on mass effects.…”
Section: Surface Stimulation Validationmentioning
confidence: 99%
“…This value was chosen based on finite element model estimates presented elsewhere and beyond which we believe capillaries within the deep tissues could be occluded [15]. A precise cut-off value, however, cannot be defined as: 1) much dispute persists still to this day with regard to capillary closing pressures (following the seminal work of Landis [18] and Kosiak [16,17], and as reviewed by Goossens [10]); 2) the effects of shear on capillary patency (discussed in companion paper I [14]) were not modeled; and 3) the relationships between surface pressures and internal compressive stresses are complex and non-linear. At the least, the value offers a benchmark for systematic comparison of the area that may remain unrelieved by stimulation and so be at increased risk of Deep Tissue Injury (DTI).…”
Section: Ppa Peak Pressure Areamentioning
confidence: 99%
“…Secondary outcome measures used to assess secondary hypotheses: 1) Tissue health would be improved, indexed by: increased muscle perfusion (acutely during stimulation, and chronically at-rest), increased muscle volume, and decreased seated pressure density at-rest, each over a 6 mo. treatment window; as well as decreased PU recurrence rate at 1 year (compared to statistical rates [4]. 2) Wound healing would be improved, indexed by increased flap wound healing and/or decreased complication rates.…”
Section: Hypotheses (Table 1)mentioning
confidence: 98%
“…The review and biomechanical analysis in companion papers I and II [3,4] highlighted the potential benefits of neuromuscular electrical stimulation (NMES) for pressure ulcer prevention (PUP). These data suggested that long-term, independent activation is required for each of the hip extensor muscle groups: gluteus maximus (GM), innervated by the inferior gluteal nerve (IGN); and hamstrings (HS), innervated by medial branches of the sciatic nerve (SN).…”
Section: Introductionmentioning
confidence: 99%